Pelatihan Pengenalan Internet Dan Microsoft Office Bagi Siswa SMP Al Mutmainnah - Valian Yoga Pudya Ardhana; M. Dermawan. Mulyodiputro (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
Teenagers are the next generation of the nation who need attention. Ways of thinking and external factors can affect the nature and can lead to juvenile delinquency. With the rapid development of the world of technology, which allows the world to be in your hands only if it is connected to the internet, which has both positive and negative impacts, so there is a need for coaching in the use of the internet. Likewise, the use of applications such as Microsoft office is very important to be given training to assist in activities at school or outside of school. For this reason, the community service team went directly to Al Mutmainnah Junior High School to provide training on how to use the internet properly and correctly and train students in the operation of Microsoft office. The results obtained in the implementation of this community service activity are that the students are very enthusiastic about participating in the training and can receive the material well so that the students of SMP Al Mutmainnah can independently use Microsoft Office in their daily activities and can use the internet properly.